Early Diagenesis of Plitvice Lakes Waterfall and Barrier Treavertine Deposits - Chafetz, Henry; Srdoc, Dusan; Horvatincic, Nada (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1994)
ABSTRACTTravertine forms spectacular waterfalls, barriers, and subaqueous finegrained lake-fill accumulations throughout the Plitvice National Park, Croatia, northwestern Yugoslavia. Barrier deposits form dams, behind which, the lakes of the Plitvice complex are situated. Three generations of low-magnesian calcite spar comprise the waterfall and barrier forming travertines. The initial precipitates generally are composed of cloudy, very finely to medium crystalline equant to bladed spar. A later generation is composed of clear, isopachous layers of medium to coarsely crystalline bladed crystals. Additionally, centimeter-thick laminated speleothem-like crusts, composed of clear, bladed to columnar spar, are the common precipitates around micritic accumulations within the older travertine. In comparison, the lake-fill deposits are primarily composed of moderately (recent lake-fill deposits) to well-developed (relict lake-fill deposits) 3-8 ^m calcite rhombohedrons. Petrographie analyses clearly show that cyanobacteria, fungi, and/or other microbial organisms bore into the spar and micritize it. This sparmicritization is pervasive throughout the waterfall and barrier deposits. Bladed spar crystals range from those which are pristine to those whose original bladed morphology can only be interpreted by comparison with laterally adjacent crystals. Individual samples display multiple generations of spar which have undergone various degrees of sparmicritization. Sparmicritization results in a thoroughly micritized accumulation in which evidence of the original spar composition has been completely obliterated.